Developing the ability to solve problems in biology of secondary 4 students with the problem-based learning management model - Sodok, Pattamamwan; Phorntaweeku, Satjatham (Journal for Developing the Social and Community, 2023)
The purpose of this research is to develop model of problem-based solving abilities learning management in biology course. The target group were 18 secondary 4 students in the second semester of the academic year 2021. The tools used in this research were 5 problem-based learning management plans, problem-solving ability assessment form, and problem-solving skills assessment form and field records. The researcher carried out the research in accordance with the Action Research along with Kurt Lewin’s concept. The data were analyzed using basic statistical values, mean, percentage and standard deviation which operated in 3 cycles. The results showed that secondary 4 students were assessed for their abilities in problem solving. They gained and passed the assessment criteria of 70% or more. This indicated that the problem-based learning management model can improve students' problem-solving abilities.